A pandemia da Covid-19 e a vulnerabilidade dos trabalhadores no/do turismo no Brasil - Claudia Corrêa de Almeida Moraes; Roberson da Rocha Buscioli; Mara Aline dos Santos Ribeiro; Fábia Trentin; Monique de Oliveira Serra (Confins)
The Covid-19 pandemic, decreed in March 2020 by the World Health Organization - WHO, generated a global crisis affecting various economic sectors of society, including tourism with a reduction in the Nominal Revenue of Tourism Characteristic Activities - ACTs, generating unemployment, concomitant to the period of implementation of the Labor Reform of 2017. The objective of this article is to know the dynamics of employment in ACTs during the Covid-19 pandemic, considered a period of exception in the national context, to understand if there were or not a deterioration in the labor vulnerability situation and on the work in tourism from the analysis of the types of contracts in force during the years 2020 and 2021 concerning workers in general. It was chosen as a methodological path the qualitative and quantitative analysis of the data collected in the New General Register of Employed and Unemployed - Novo Caged, by analyzing the balance of jobs in the ACTs, the profile of temporary and intermittent contracts from the variable gender in the mentioned period. Finally, the negative balance of jobs as a result observed in the first wave did not recover in the following period of the resumption of activities in the sector. As for precarious contracts, it was observed that these had a higher compound growth rate than those for an indefinite period, in which women were the majority.